Application of Photodynamic Therapy in Patients with Generalized Periodontitis - Danko Е. М.; Kostenko Є. Я.; Pantio В. В. (Actual Dentistry, 2024)
Topicality. Periodontitis is a chronic infectious disease requiring a comprehensive diagnosis and treatment approach. Traditional treatment protocols do not always bring the desired clinical results, as the pathogenic microflora of periodontal pockets are resistant to used antimicrobial agents. Therefore, there is a need to find alternative comprehensive methods of treating periodontitis, in particular, the use of non-drug agents, such as photodynamic therapy (PDT). PDT is a new, non-invasive treatment method that is widely used in the treatment of both oncological and non-oncological diseases. Antimicrobial PDT, due to its bactericidal effect on opportunistic and pathogenic oral cavity microflora, is considered an alternative and complement to traditional therapy for periodontal tissue diseases. It has been described that using PDT, together with traditional therapy methods, significantly improves the results of periodontal treatment. However, the justification for the choice of low-intensity radiation and its parameters, namely wavelength, polarization, exposure, and power, as well as the effect of methylene blue concentration on periodontal tissues during PDT, remain incompletely studied. The work aimed to determine and compare the effect of the photosensitizer 0.1% aqueous solution of methylene blue and low-intensity LED and PILER (Polarized Incoherent Low-Energy Radiation) radiation without the use of antibiotic therapy on periodontal tissues and the indices of the index assessment of the state of periodontal tissues, papillae bleeding index and depth of periodontal pockets in the complex treatment of patients with chronic generalized periodontitis of stages I-II and the use of a generally accepted treatment method. Materials and methods. During the study, 86 patients with chronic generalized periodontitis of stages I–II were treated at the University Dental Clinic of the Faculty of Dentistry of the State Higher Educational Institution “Uzhhorod National University.” Patients were divided into three groups: Group 1 consisted of 22 patients who were treated according to the generally accepted treatment protocol using the SRP method; Group 2 (n = 31) — which additionally underwent PDT using a 0.1% solution of methylene blue and PILER (Polarized Polychromatic Incoherent Low-Energy Radiation) radiation with a red light filter (λ = 625–740 nm) without antibiotic therapy and Group 3 (n = 33) which additionally underwent PDT using a 0.1% solution of methylene blue and LED radiation using the “Medolight-RED” device in the red-infrared ranges (λ = 640 ± 30 and 880 ± 30 nm) without antibiotic therapy. The assessment of the results of the treatment in all groups was determined using the PMA, Fedorov-Volodkina indices, the papilla bleeding index, and the depth of periodontal pockets were determined on the 14th day of treatment, 3 months, and 6 months after treatment. Results of the study and their discussion. After complex treatment, all indicators improved in all groups. At the same time, the indicators of the index assessment of periodontal tissues and the depth of periodontal pockets were significantly better in Groups 2 and 3, where PDT using low-intensity radiation was used. Thus, after 6 months, the PMA index of Group 3 was 11.94 ± 2.05, which is 1.2 times better compared to Group 2 (13.01 ± 1.85) and 2 times better than Group 1 (24.5±3.64), the Fedorov-Volodkina index in Group 3 was 1.26 ± 0.13, which is almost similar to the indicators of Group 2 (1.28 ± 0.15) and 1.4 times less than Group 1 (1.8 ± 0.59). The PBI index was approximately the same in Groups 2 and 3 and was 0.33 ± 0.21 and 0.32 ± 0.19, respectively, almost 4 times less than the data of Group 1 (1.27 ± 0.63). PPD in Group 3 after 6 months was 2.44 ± 0.34, which is 0.05 mm less than Group 2 (2.49 ± 0.32) and 0.64 mm less than Group 1 (3.08 ± 0.32). Conclusions. The use of low-intensity radiation and photosensitizer methylene blue in the complex therapy of chronic generalized periodontitis resulted in better and faster treatment results compared to the control group’s data, where only the generally accepted treatment protocol with the use of SRP was used. The results of the study indicated that the use of PDT using both PILER and LED radiation in the complex treatment of generalized periodontitis of stages I–II has a positive effect on the dynamics of hygiene indicators, index assessment of the state of periodontal tissues, and the depth of periodontal pockets.